Implementation of Essential Newborn Care and Factors Associated with Knowledge and Practices among Postnatal Mothers in the Slum Area of Karachi, Pakistan - Mehrozia Nuzhat; Asma Noreen; Mehtab Hussain; Imrana Ata; Nadeem Noor; Falak Abro; Bushra Rafique (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To determine the implementation of essential newborn care (ENC) and factors associated with knowledge and practices among postnatal mothers in the Slum Area of Karachi, Pakistan. METHODOLOGY: This cross-sectional study was conducted in the outpatient and inpatient departments, postnatal ward/well baby clinic/immunization clinic, Jinnah Medical College Hospital (JMCH), Karachi, Pakistan, from January - June 2024. A total of 233 postnatal mothers aged between 18-35 years, within 2 months after delivery, and without complications who delivered babies (gestational age 38-42 weeks) without any congenital anomalies or disability were analyzed. A non-probability consecutive sampling technique was adopted. Data about ENC was collected on a structured and comprehensively validated questionnaire. Data was analyzed using IBM-SPSS Statistics, version 26.0. RESULTS: In a total of 233 participants, the mean age was 26.27±4.69 years. 54 (23.2%) received health education on ENC during pregnancy, and 167(71.7%) after delivery. Fifty (21.5%) mothers practiced skin-to-skin contact, and 161(69.1%) delayed the first bath for more than 24 hours. The time of initiation of breastfeeding was within one hour, found in 70(30.0%) participants. Washing hands before and after 54(23.2%) mothers reported diaper changes. 108 (46.4%) mothers reported recognition of all danger signs. CONCLUSION: The study concludes that implementing ENC among postnatal mothers in the slum area of Karachi is sub-optimal, with significant gaps in knowledge and practices. Key areas requiring improvement include antenatal care attendance, hygiene practices, and late initiation of breastfeeding.